Analisis Kepuasan Pengguna Terhadap Fitur REHAB pada Aplikasi Mobile JKN dengan Menggunakan Metode UEQ - Ali, Abdurrahman; Kadafi, Muhamad (TIN: Terapan Informatika Nusantara, 2025)
BPJS Kesehatan, as the organizer of the National Health Insurance (JKN), continues to strive to improve service quality and ease of access for its participants through technology-based innovations. In 2024, the Mobile JKN Application has been downloaded more than 40 million times on Google Play Store, providing convenience for 276.9 million people registered as JKN participants to access effective healthcare services. This study focuses on analyzing user satisfaction with the REHAB feature on the Mobile JKN Application using the User Experience Questionnaire (UEQ) method. UEQ consists of six evaluation aspects: Attractiveness, Perspicuity (Clarity), Efficiency, Dependability, Stimulation, and Novelty. The study employed a questionnaire-based testing method, UEQ, which lasted for one month. The research targeted residents of Palembang City who use the REHAB feature on the Mobile JKN Application, with a total of 131 respondents. For the dimensions of attractiveness, clarity, efficiency, accuracy, stimulation, and novelty, the obtained scores were above 0.8, indicating above-average ratings. This suggests that, overall, user evaluation of the REHAB feature on the Mobile JKN Application is positive. Based on the evaluation conducted using the UEQ method, which assesses user experience across six scales, the aspects of attractiveness, clarity, efficiency, and accuracy received excellent ratings. This indicates that the REHAB feature is highly appealing, easy to understand, efficient, and effective in meeting user needs.